2022
DOI: 10.5603/fm.a2021.0024
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the hepatic artery: a closer view of rare unclassified variants

Abstract: Background: Defining the hepatic artery anatomy is of great importance for both surgeons and radiologists. Michel classification was designed to classify hepatic artery variations. Nevertheless, there are variations that do not fit into this classification. In this study, we aim to define the incidence of all variations in a healthy liver donor by reviewing their CT scan with special emphasis on variations that do not fit in any of the Michel classes. Materials and methods: A retrospective analysis of CT scan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 11 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…We found that the classic Hiatt and Michel classifications were unsuitable for these rare and complex classifications, and their coverage by the CRL classification was relatively improved, but the specificity for these rare cases was not high. For example, rRHA described by Abdullah et al ( 33 ) in 2006 originated from the inferior mesenteric artery, which is classified as CR rOM L by ex-CRL, and rRHA described by Imam et al ( 25 ) in 2021 was derived from the pancreaticoduodenal artery, which was classified as CR rOD L by ex-CRL, but both cases are represented by CRL classification as “2o (CR rO L)”. The CRL classification does not clearly describe this part of “other arteries”, making it necessary to use ex-CRL for reclassification.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the classic Hiatt and Michel classifications were unsuitable for these rare and complex classifications, and their coverage by the CRL classification was relatively improved, but the specificity for these rare cases was not high. For example, rRHA described by Abdullah et al ( 33 ) in 2006 originated from the inferior mesenteric artery, which is classified as CR rOM L by ex-CRL, and rRHA described by Imam et al ( 25 ) in 2021 was derived from the pancreaticoduodenal artery, which was classified as CR rOD L by ex-CRL, but both cases are represented by CRL classification as “2o (CR rO L)”. The CRL classification does not clearly describe this part of “other arteries”, making it necessary to use ex-CRL for reclassification.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric solid organ transplantation (SOT) is the treatment of choice for end-stage organ failure (Imam et al, 2020), which allows the medical situation of a child to change from experiencing a lifethreatening disease to having a chronic health condition (Annunziato et al, 2012). Caregivers are an essential figure in SOT; even so, we still have limited understanding of the experience of caregiving through the entire process of transplantation, and there are limited data examining the long-term impact.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic artery variations were studied in detail by various researchers and given the internationally accepted classification. The classification given by Michel and Hiatt is the most popular and acceptable [ 3 , 4 , 5 ]. Michel classified hepatic artery variations into 10 different types and Hiatt classified them into six different types [ 4 , 5 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The classification given by Michel and Hiatt is the most popular and acceptable [ 3 , 4 , 5 ]. Michel classified hepatic artery variations into 10 different types and Hiatt classified them into six different types [ 4 , 5 ] ( Table 1 ). According to both, Type I variation is the most common and represents regular branching of the hepatic artery [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation